Efeitos de ensino de multiplicação por meio do ensino por matriz na emergência de respostas recombinadas - Picharillo, Alessandra Daniele Messali (Universidade Federal de São Carlos, 2024)
With the technological advances present in society, education can take advantage of the benefits that the attractions of virtual environments have and, thus, promote conditions that enhance student learning. The main objective of this study was to verify the effects of matrix teaching on multiplication learning on the generativity of new mathematical repertoires with the additional objective of evaluating the effectiveness of the Besouriz computerized tool. 26 students aged between seven and 11 years-old participated in this study, being 16 with typical development and 12 with Autism Spectrum Disorder, enrolled in regular education or in a specialized institution. A written pre- and post-test design was used to assess multiplication repertoire. A multiple probe between stimulus groups design was also used. The independent variable was teaching multiplication through additive equivalent, using matrix training. The dependent variable was the participants' performance in the repertoire taught and assessed in written tests. The multiplication tables of one, two and three were taught. The results indicate that the game was efficient and effective regardless of the input repertoire, age and neurodevelopment condition. It is suggested that the study be expanded to other groups of special education students.
Effects of teaching multiplication through matrix teaching in the emergency of recombined responses
Keywords: Educação especial; Jogo educativo; Matemática; Transtorno do espectro do autismo; Matriz; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM